PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PENGGUNA SEPEDA MOTOR HONDA DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Jazuli, Mohammad Hasan; Hamdun, Edy Kusnadi; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aimedat describing the effects of brand image and product quality on consumer satisfaction with Honda motorcycle users in the Faculty of Economics and Business, Universitas Abdurachman Saleh Situbondo with purchase decision as the intervening variable. The sampling technique used in this study was proportional stratified random sampling using the Slovin formula, with a tolerable error rate of 10%. The number of samples in this study were 87 students. Analysisdata and hypothesis testing in this study employed the Structural-Partial Equation ModelLeast Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that brand image has a positive and significant effect on purchasing decisions, product quality has apositive and significant effect on purchasing decisions, brand image has a positive and significant effecton consumer satisfaction, and product quality has a negative and not significant effect on consumer satisfaction. Meanwhile, purchase decisions have a positive and significant effect on satisfactionconsumers, brand image has a positive and significant effect on consumer satisfaction through purchase decisions, and product quality has a positive and significant effect on consumer satisfactionthrough purchasing decisions.